Bioengineering of the model lantibiotic nisin - Field, Des (Bioengineered, 2015)
The lantibiotics are a class of bacterially produced antimicrobial peptides (bacteriocins) that contain several unusual amino acids resulting from enzyme-mediated post-translational modifications. They exhibit high specific activity against Gram-positive targets, including many antibiotic-resistant pathogens, and consequently have been investigated with a view to their application as antimicrobials in both the food and medical arenas. Importantly, the gene-encoded nature of lantibiotics makes them more amenable to bioengineering strategies to further enhance their antimicrobial and physicochemical properties. However, although the bioengineering of lantibiotics has been underway for over 2 decades, significant progress has only been reported in recent years. This review charts recent developments with regard to the implementation of bioengineering strategies to enhance the functional characteristics of the prototypical and most studied lantibiotic nisin.